The Florida Bull Test 2014–2015 - Carla D. Sanford; G. Cliff Lamb; Nicolas DiLorenzo (EDIS)
The 2014-2015 Florida Bull Test concluded with the evaluation of 103 bulls. The test assessed the performance potential and breeding soundness of bulls consigned to the program at the UF/IFAS North Florida Research and Education Center (NFREC). This 9-page fact sheet covers the test procedures, feed efficiency assessment, test rules and regulations, health requirements, test results, and sale summary. Written by Carla D. Sanford, G. Cliff Lamb, and Nicolas DiLorenzo, and published by the UF Department of Animal Sciences, June 2016.